The manuscripts of Leo the Great's letters: the transmission and reception of papal documents in Late Antiquity and the Middle Ages - Hoskin, Matthew J. J. (Instrumenta patristica et mediaevalia, 2022)
This book explores the transmission of the letters of Leo the Great (pope, 440-461). After setting out the contours of Leo's papacy and the factors contributing to the sending and subsequent transmission of his letters to posterity, it deals in detail with around sixty collections of Leo's letters and over 300 manuscripts ranging in date from the sixth up to the sixteenth century. Each period of the Middle Ages is introduced as the context for collecting and copying the letters, and the relationships between the letter collections themselves are traced. The result is a survey of the impact of Leo the Great upon Latin Christendom, an impact that was felt in theology and canon law, especially from the age of the Emperor Justinian to the Council of Ferrara-Florence, and moving through the major monasteries of Europe from Corbie to Clairvaux. At every cultural Renaissance, Leo was a presence, being copied, rearranged, interpreted, and eventually printed. This book is a testament to the legacy of one of the mid-fifth century's most influential figures